Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction